Scattering of the Edge-guided Wave by an Edge Crack at a Circular Hole in an Isotropic Plate. (2017) - Chiu, W.K.; Rose, L.R.F.; Vien, B.S.
Abstract: Reliable and quantitative detection of a small fatigue crack at hard-to-inspect locations remains a challenging problem for structural health monitoring. A small crack emanating from the blind side of a fuel weep hole constitutes a representative example where traditional non-destructive methods fail, and a new approach is required. Recently Lamb-wave inspection has emerged as an attractive method due to their advantageous properties of low geometrical decay and rapid wide-area coverage. This paper presents a computational study of the interaction between the edge-guided wave and small crack on a circular hole in an aluminium plate. Edge-guided waves are generated by applying forces on the circumference whose time dependence is a 5.5 Hann-windowed toneburst of centre frequency below the cut-off for the first-order Lamb wave modes (A1 and SH1). It is shown that edge waves travelling on the curved surface leak energy into the medium, unlike those travelling on a straight surface which do not attenuate, and the scattered field generated by their interaction with an edge crack is investigated. A 2D Fast Fourier Transformation (2D FFT) is used to produce the dispersion curve to identify the scattered Lamb wave modes. In this investigation the hole diameter, d, is larger than incident wavelength, λ, ( d/λ >1) and for small crack size approximation the crack length, a, is smaller than the incident wavelength, a/λ <1, and the hole diameter, a/d <1. The scattering pattern and amplitude on crack size are reported. The application of these forward-scattering results for addressing the inverse problem of crack detection and sizing are briefly discussed.